Book Review: The Art Of Loving - Aritonang, Delinda Elizabeth; Valentin, Michel (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
This phenomenal book, which has been translated into 42 languages, was written by Eric Fromm. The content presents a discussion of the meaning of love as a human existence that has a productive orientation. In this book Fromm highlights the theory and issues of love in human relational life. This book, which has an international bestseller award, convinces its readers that all efforts to achieve love will fail if a person does not first develop his entire personality; that the fulfillment of one's love can only be achieved with the ability to love others, with humility and determination, as well as faith and discipline. This fact prompted Fromm to propose 4 parts in the form of critical statements which became the main analysis in his book. First, what is Love? Second, the theory of love. Third, Love and Its Destruction in Contemporary Western Society. And finally, the Practice of Love. Fromm in this book uses several analytical perspectives including: psychology, philosophy, historical, social, economic and cultural. Thus, through this book these statements will be revealed in full. Through this book, the author evaluates the importance of love in the relational life of Christians in the era of digitalization. According to Erich Fromm, the concept of love in this book is the right solution to overcome the isolation and loneliness experienced by modern humans, because it is in accordance with the nature of human existence.